Screening of antioxidant, anti-acetylcholinesterase and antifungal activities and HPLC-MS identification of the bioactive phenolics of Eclipta alba (L.) Hassk. - Guenné Samson; Hilou Adama; Meda Nag Tiero Roland; Ouattara Nabèrè; Tiendrebéogo Martin; Millogo-Rasolodimby Jeanne; Nacoulma Odile Germaine (International Journal of Phytomedicine, 2012)
Eclipta alba is commonly used in traditional medicine for several ethnobotanical properties. Researchers have isolated several bioactive compounds of this plant. In Burkina Faso, this medicinal plant is mainly used for its antifungal properties. Our study aimed to evaluate the antioxidant, acetylcholinesterase inhibitory, antifungal activities and to quantify polyphenols from Eclipta alba extracts using HPLC-MS. The crude extract (CE) and fractions of this plant were used for these activities through standard methods. Ethyl acetate fraction (EAF) and acetonitrile fraction (ACNF) have been the potential inhibitors of the liver lipids peroxidation (According to the thiobarbituric acid method) with the percentages of 65.48% and 65.13%, respectively. Concerning the ABTS radical cation scavenging capacity descript by Guenné, ACNF (67.28 mg T/g of extract) and butanol fraction (BF) (66.03 mg T/g of extract) have presented the highest activities. BF has also presented an interesting acetylcholinesterase (AChE) inhibitory activity with a percentage of 55.82%. For antifungal activity, the crude extract and ACNF have given the better MIC values against C. albican and T. beigelii with a concentration of 1.25 mg/mL using microplate method descript by Eloff. The strain C. krusei was only sensitive to butanol fraction. The polyphenols identified and quantified using HPLC-MS are: gentisic acid, caffeic acid, chlorogenic acid, p-coumaric acid, apigenin, luteolin and quercetin. The butanol fraction of E. alba presented the best activities for the tests performed; this fraction is a good ways to isolate new anti-fungal and anti-acetylcholinesterase compounds.